Democracy in America and two essays on America - Tocqueville, Alexis (London Penguin Books, 2003)
In 1831 Alexis de Tocqueville, a young French aristocrat and ambitious civil servant, set out from post-revolutionary France on a journey across America that would take him 9 months and cover 7,000 miles. The result was Democracy in America, a subtle and prescient analysis of the life and institutions of 19th-century America. Tocqueville looked to the flourishing deomcratic system in America as a possible model for post-revolutionary France, believing that the egalitarian ideals it enshrined reflected the spirit of the age and even divine will. His study of the strengths and weaknesses of an evolving democratic society has been quoted by every American president since Eisenhower, and remains a key point of reference for any discussion of the American nation or the democratic system.
Keywords: Democracy-US